2002
DOI: 10.1089/15305620260507495
|View full text |Cite
|
Sign up to set email alerts
|

Self-Regulation Training for Chronic Pain: Can It Be Done Effectively by Telemedicine?

Abstract: The purpose of this project was to test the efficacy of behavioral telemedicine interventions designed to teach self-regulation skills to chronic pain patients who had not previously been treated. The study sought to determine whether there were differences in outcome and consumer satisfaction with the pain management intervention when delivered by conventional face-to-face methods, by telephone only, and by closed circuit TV (CCTV). We found that self-regulation techniques can be readily taught via behavioral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 22 publications
0
23
0
1
Order By: Relevance
“…Overall the findings are very encouraging, with patients and therapists reporting positive perceived benefits, convenience and usefulness of the telerehabilitation program. The only study to report any problematic area from the patient's point of view found moderate satisfaction with the interpersonal relationship between patient and therapist [26]. Main complaints from therapists were related to the quality of video transmission [24,27,28], scheduling issues [24], and difficulties in using the technology with certain clienteles such as active or shy children [28].…”
Section: Findings Relating To Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall the findings are very encouraging, with patients and therapists reporting positive perceived benefits, convenience and usefulness of the telerehabilitation program. The only study to report any problematic area from the patient's point of view found moderate satisfaction with the interpersonal relationship between patient and therapist [26]. Main complaints from therapists were related to the quality of video transmission [24,27,28], scheduling issues [24], and difficulties in using the technology with certain clienteles such as active or shy children [28].…”
Section: Findings Relating To Satisfactionmentioning
confidence: 99%
“…Rehabilitation for multiple clienteles (n ¼ 4) [25,26,36,59] Findings limited to one study of behavioural intervention, found no significant difference in relaxation and pain between face-to-face and video conference. Study done in clinical setting with therapist and patient in separate rooms.…”
Section: Not Reportedmentioning
confidence: 99%
“…1 Telemedicine has been used successfully in a few specialties, such as psychiatry and cardiology, for counselling and monitoring of treatment response. 2,3 However, TM is relatively new to other medical disciplines. It relies on high-speed, high-bandwidth telecommunication systems that allow two-way real-time clinical consultations over an audio-video link augmented by other modalities, such as an electronic stethoscope and a high-resolution image viewer.…”
Section: Résumémentioning
confidence: 99%
“…Notable also is the use of self-management methods in an on line format, with a literature that has progressed from case studies and uncontrolled feasibility testing [1,11] to randomized clinical trials [7,29,44]. Although early applications of interventions labeled ‘self-management’ tended to focus on biofeedback methods [40], contemporary approaches attempt to educate persons with pain in a variety of skills and motivational strategies presumed necessary for self-guided symptom management and everyday task persistence.…”
Section: Introductionmentioning
confidence: 99%